The unseen world Christian reflections on angels, demons, and the heavenly realm - Lane, Anthony N. S. (Grand Rapids Baker Books House, 1996)
"This intriguing collection features an international perspective, as scholars from America, Australia, Great Britain, and Zaire explore the invisible realm and present new insights about the nature of this unseen world." "The essays provide broad cover
Keywords: Angels -- Christianity. Demonology. Het Onzienlijke. Engelen. Demonen